SECONDARY STUDENTS PERFORMANCE IN ENGLISH VIRTUAL ENVIRONMENT AT ACULMAITL SCHOOL MEXICO. - Marisol Márquez Martínez; Arjulayana - - (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this research was to relate the extent to which the virtual learning environment improved the English language performance of first-year secondary school students in Mexico. This research had a quantitative approach with a correlational and explanatory scope to see how the variables were related, observing how reliable a virtual environment could be. In short, the importance of the study is that students develop digital skills and knowledge, so that they could take advantage of the content and make use of the digital teaching materials and resources presented on the platform. The study was carried out using non-probabilistic sampling since the subjects are 11 adolescents from the 1st year of secondary school, and they were chosen for using the platform during the school year. Taking into consideration different factors such as the individual and the context they live in. On the individual development, to cognitive variables such as learning style, prior learning, intelligence, and learning, while the latter involves motivational variables. In the context, there are three variables: the first is institutional re-use, the school centre, the school management, teacher training, and the school environment.